Genetic Diversity of Bio-fortified Lentils (Lens culinaris Medik.) through Simple Sequence Repeat Markers (SAARC Journal of Agriculture, 2023)
Nepalese lentils are comparatively rich in iron and zinc, making it a potential crop of whole food solution to aid in the global battle against the micronutrient malnutrition. Understanding the genetic basis for uptake of grain iron and zinc is required to increase their stable concentrations along with these minerals in lentils. This study aimed at characterizing genetic variation in micronutrient high grain iron and zinc concentrations and exploring the potential in lentil accessions. A set of 25 lentil accessions was evaluated in two seasons across the three locations and genotyped by using 40 simple sequence repeat (SSR) markers that are linked with lentil iron and zinc concentrations. Out of the 40 SSR markers, 23 markers were found polymorphic while 12 were monomorphic, and 5 markers were null. These 23 polymorphic markers produced a total of 584 alleles, of which 52 were polymorphic alleles, and average alleles per locus was 11.49. The linkage disequilibrium (LD) analysis was done using a mixed linear model (MLM) that identified three SSR markers, PBALC 13, PBALC 206, and GLLC 563, associated with grain Fe concentration, explaining 9% to 11% phenotypic variation, respectively, and four SSR markers (PBALC 353, SSR 317–1, PLC 62, and PBALC 217) associated with grain Zn concentration, explaining 14% to 21% phenotypic variation, respectively. The pairwise genetic similarity index among 25 lentil accessions varied from 0.16 to 0.83. The identified SSRs exhibited consistent performance across two seasons and have potential for utilization in lentil molecular breeding program.SAARC J. Agric., 21(2): 27-40 (2023)